2021
DOI: 10.3389/feart.2021.712566
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Studies and Analyses on the Acidizing Process in Vug Carbonate Rocks

Abstract: A vug porosity system, in addition to a matrix, is also the target rocks for the acidizing. In this work, the acidizing process in two typical core-scale separate-vug porosity systems is studied in detail. Numerous cases are conducted to discuss a parametric study on the acidizing process and hydraulic behavior. Results indicate that the presence of vug reduces the pore volume of acid solution consumed to achieve a breakthrough, which is consistent with experimental observations. Increasing the vug diameter an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…Qi et al [54] regarded fractures as matrices with specific high porosity and utilized COMSOL software to explore the influence of fracture geometry on the initiation and propagation of wormholes. Through parameter sensitivity analysis, Jia et al [55] examined the reaction flow processes of two typical core scales of vugular carbonate rocks as well as isolated vug carbonate rocks. They found that the vug filling degrees and vug diameter all had a significant effect on the reactive flow of fluids in carbonate rocks.…”
Section: Introductionmentioning
confidence: 99%
“…Qi et al [54] regarded fractures as matrices with specific high porosity and utilized COMSOL software to explore the influence of fracture geometry on the initiation and propagation of wormholes. Through parameter sensitivity analysis, Jia et al [55] examined the reaction flow processes of two typical core scales of vugular carbonate rocks as well as isolated vug carbonate rocks. They found that the vug filling degrees and vug diameter all had a significant effect on the reactive flow of fluids in carbonate rocks.…”
Section: Introductionmentioning
confidence: 99%
“…Some efforts have been made to investigate the influence of fractures and vugs on dissolution dynamics (Kalia and Balakotaiah, 2009;Izgec et al, 2010;Liu et al, 2017aLiu et al, , 2017bHuang et al, 2020;Wang et al, 2020;Jia et al, 2021b). Kalia and Balakotaiah (2009) considered fractures and vugs as a matrix with abnormally high porosity and evaluated the role of their location in pattern formation.…”
Section: Introductionmentioning
confidence: 99%